2020
DOI: 10.1101/2020.06.14.150425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

β-actin dependent chromatin remodeling mediates compartment level changes in 3D genome architecture

Abstract: β-actin is a crucial component of several chromatin remodeling complexes that control chromatin structure and accessibility. The mammalian Brahma-associated factor (BAF) is one such complex that plays essential roles in development and differentiation by regulating the chromatin state of critical genes and opposing the repressive activity of polycomb repressive complexes (PRCs). While previous work has shown that β-actin loss can lead to extensive changes in gene expression and heterochromatin organization, it… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The nuclear genome is hierarchically organized into A and B compartments which respectively correlate with open and closed chromatin or euchromatin and heterochromatin (Fortin and Hansen, 2015). We recently reported that loss of nuclear actin leads to compartment switching, in turn leading to differential expression of genes present within these compartments (Mahmood et al, 2021). Mitochondrial genes tend to cluster together and are often found in the pericentromeric and subtelomeric regions, which are characterized by lesser chromatin accessibility and heterochromatinization (Moon et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear genome is hierarchically organized into A and B compartments which respectively correlate with open and closed chromatin or euchromatin and heterochromatin (Fortin and Hansen, 2015). We recently reported that loss of nuclear actin leads to compartment switching, in turn leading to differential expression of genes present within these compartments (Mahmood et al, 2021). Mitochondrial genes tend to cluster together and are often found in the pericentromeric and subtelomeric regions, which are characterized by lesser chromatin accessibility and heterochromatinization (Moon et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The nuclear genome is hierarchically organized into A and B compartments which respectively correlate with open and closed chromatin or euchromatin and heterochromatin (Fortin and Hansen, 2015). We recently reported that loss of nuclear actin leads to compartment switching, in turn leading to differential expression of genes present within these compartments (Mahmood et al, 2021).…”
Section: Nm1 Regulates Mitochondria By Regulating Specific Mitochondr...mentioning
confidence: 99%
“…Because jasplakinolide also directly affects nuclear actin, which is required for HC dynamics (Mahmood et al, 2020;Xie et al, 2018aXie et al, , 2018b, we generated a genetic model of mechanical stress based on cytoplasmic F-actin hyperpolymerization by Actin capping protein-b (Cpb) knockdown. In fly brains, neuronspecific cpb RNAi caused cytoplasmic F-actin hyperpolymerization (Figure 5D), and, similar to knockout of its ortholog Capzb in mice (Pocaterra et al, 2019), was associated with actomyosin hypercontraction, as shown by phosphorylation of Spaghetti squash (Sqh; the ortholog of MLC-2 [myosin light chain-2]) (Figure S5F), leaving Dodo protein levels unaffected (Figure S5G).…”
Section: Figure 2 Dodo Restrains Te Activity In Drosophila Brainsmentioning
confidence: 99%
“…Actin could be one possible candidate to regulate these global changes in chromatin organization during differentiation. Indeed, mouse embryonic fibroblasts (MEFs) lacking the β-actin gene display altered 3D genome architecture (Mahmood et al, 2021) and are defective in their reprogramming capacity towards osteoblast-like cells (Gjorgjieva et al, 2020), adipocytes (Al-Sayegh et al, 2020) and chemical-induced neurons. In this latter case, β-actin deficiency is linked to loss of chromatin-binding of Brg1, an ATPase of the BAF chromatin remodeling complex.…”
Section: Discussionmentioning
confidence: 99%